Evaluation of tools and cutting conditions on carbon fibre reinforced laminates - Gonçalves, Daniel J. S. (2014)
The distinctive characteristics of carbon fibre reinforced plastics, like low weight or high specific strength, had broadened their use to new fields. Due to the need of assembly to structures, machining operations like drilling are frequent. In result of composites inhomogeneity, this operation can lead to different damages that reduce mechanical strength of the parts in the connection area. From these damages, delamination is the most severe. A proper choice of tool and cutting parameters can reduce delamination substantially. In this work the results obtained with five different tool geometries are compared. Conclusions show that the choice of an adequate drill can reduce thrust forces, thus delamination damage.